PENANGANAN DAN PENYELESAIAN KONFLIK PADA RESTRUKTURISASI KANTOR PELAYANAN TERPADU SERTA IMPLIKASINYA TERHADAP KETAHANAN EKONOMI WILAYAH (Studi Tentang Pelayanan Perizinan Pada Badan Penanaman Modal Dan Pelayanan Perizinan Kabupaten Pacitan, Jawa Timur) - Purwoko Juli Sasmito (Jurnal Ketahanan Nasional, 2014)
Modal Investment and Permitting Service Institution Institution’s (BPM and PP) at Pacitan Regency restructure had affected the organization structure, duty and authority, services’ type and the amoun of the staff. The Integrated Service Office at the Pacitan Regency BPM and PP restructure’s conflict consisted of two parts, namely the conflict of BPM and PP with other institution and the internal conflict of Pacitan Regency BPM and PP. The purpose of this research was to discovered the integrated service office restructure’s conflict management and resolution and its implication on regional economic resilience. This research was conducted with in depth interview, field survey, and questionnaire method. The collected data were analyzed. The Pacitan Regency BPPM and PP conflict was at the normal level, therefore it could be well managed and able to developed into positive conflict. The threat over regional economic resilience is open conflict potential.Keywords: Conflict, Restructuration, Economic Resilience of Region